Auditory Processing of the Brain Is Enhanced by Parental Singing for Preterm Infants - Partanen, Eino; Mårtensson, Gustaf; Hugoson, Pernilla; Huotilainen, Minna; Fellman, Vineta; Ådén, Ulrika (Frontiers in Neuroscience, 2022)
As the human auditory system is highly malleable in infancy, perinatal risk factors, such as preterm birth, may affect auditory development. In comparison to healthy full-term infants, preterm infants show abnormal auditory brain responses at term age, which may have long-term detrimental outcomes. To achieve an optimal neonatal care environment for preterm-born infants, many early interventions have been developed. Musical interventions developed for neonatal intensive care units (NICUs) have shown beneficial effects on vital functions and weight gain of preterm infants and might also influence basic auditory processing and thereby enhance outcomes. In the present study, we tested the effect of parental singing during kangaroo care on auditory processing of standardized audio stimuli. Preterm infants (born between 24 and 32 weeks of gestation) were randomized to singing intervention (n=13) or control (n=8) groups. The auditory processing was tested using two audio paradigms assessed with magnetoencephalography (MEG) at term corresponding age. To verify that the paradigms elicit responses in MEG, we studied 12 healthy full-term infants. In the singing intervention group, parents were instructed by a music therapist twice a week for four weeks to sing or hum during kangaroo care in an infant-directed way. The control group received standard kangaroo care. The results show that the infants in the singing intervention group show larger neural responses than those in the control group when controlling for the total amount of singing during kangaroo care. Our findings suggest that incorporating singing into kangaroo care may be beneficial for preterm infants, but the effect may not be due to exposure to singing but instead positive parenting, improved parental self-esteem and improved caregiver sensitivity.